Community-Driven Development in Local Government Capacity Building Projects : Emerging Approaches in Africa - Kuper, Kate (World Bank, Washington, DC, 2012)
This note discusses the interface between community-driven development (CDD) and decentralization. In particular, it focuses on the aspects of decentralization programs related to local government capacity building, where the practical application of CDD principles becomes meaningful. The note considers how the principles of CDD are being incorporated into local government capacity building projects, and examines where potential limitations may exist. It does not intend to be a comprehensive review of either CDD or decentralization but rather to use a few examples, especially in projects under preparation or implementation in Africa, as illustrative of this emerging approach.